Analisis Simulasi Monte Carlo untuk Memprediksi Penjualan Basreng pada Toko XYZ - Novita, Triana; Muhammad, Hafizh (Jurnal TEFSIN ( Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Micro, small and medium enterprises (MSMEs) are one of the pillars of the current economy because they help the community and increase employment opportunities. MSMEs usually only reach an area, so if the area's MSMEs are developed then the surrounding community will also prosper, and vice versa. Even though it is only MSMEs in a region, it does not rule out the possibility of selling products/services to other regions or even abroad, one of which is by utilizing online-based sales. However, for food products, buyers usually prefer to go directly to the shop compared to ordering online because it takes time and there is a risk of damaged packaging and so on. Good sales are inventory that is always available and measurable both in offline and online sales. Therefore, the form of this system is to present information from data on the number of product sales using the Monte Carlo simulation method in the MSME industry of XYZ shop, the aim of which is to predict income and inventory of goods from sales of each product for the following month. In essence, this system is designed to predict gross profit on each type of item in the store. With this system, it is hoped that it can be used by the MSME industry to simulate the sale of goods in shops, and can make it easier for MSME industry owners to obtain information about the possibilities that will occur in the sale of their products.